Primary Caesarian Section in El-Obeid Town, West of Sudan - E.Maruod, Maruod; Awadalla MD, Dr. Khidir Elamin; Abdellatif MD, Dr. Rawaa Kamal; Gerais MD,, Prof. Abdelsalam (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
The name caesarian section or caesarian delivery, means surgical removal of a fetus from the uterus, through abdominal and uterine incisions, following the completion of 28 weeks of pregnancy.  It is called primary caesarian section when it is done for the first time. Though caesarian delivery is associated with increased risk of maternal and neonatal morbidity and mortality compared to vaginal birth. The Objectives of the study were to review current incidence, indications and outcome of primary caesarian section. To calculate incidence of primary caesarian section in El-Obeid , West of Sudan. To analyze indications for primary caesarian section and to evaluate the fetal and maternal outcome following the operation. The methodology was a prospective descriptive hospital-based  study, conducted  in  El-Obeid Town among pregnant ladies undergoing primary caesarian section in the main four Hospitals, which are El-Obeid Maternity Hospital, Police Hospital , Kordofan  Specialized Hospital  and  El-Obeid  Military  Hospital. The study involved all pregnant ladies booked for primary caesarian section in the four hospitals during the period first of July to 31st December 2013.The results showed that the number of cases who had a primary C/S were  612. Total number of life -birth deliveries were 4212 and incidence of primary C/S was 14.5 %. The  indication were  failure to progress 269 cases (43.9%) ,  fetal distress 98 cases (16%) , breech presentation 72 cases (11.8%) , pre-eclampsia /eclampsia 50 cases (8.2%) ,  abnormal lie and  presentation 40 cases (6.6%) , flailed induction of labor 35 cases (5.7%) , antepartum hemorrhage 34 cases (5.6%) , maternal request 7 cases (1.1%) ,and other indications 7 cases (1.1%). Three hundreds of the cases were primiparae .The operation was an elective procedure in 362 cases (59.15%) .  Spinal anesthesia was used  in 576  cases  (94.1%) , general anesthesia in 32  and only 4 cases with local infiltration .  Average hospital stay was 3.5± 2.1 days. Neonatal adverse outcome was encountered in 55 of the deliveries (9.0%). Maternal morbidity occurred in 50 cases (8.2 %).Conclusion: The study provided important data which can help in formulation ofRecommendations to reduce the rate of primary C/S as well as morbidities. The main maternal complications were found to be postpartum haemorrhage and sepsis, while fetal complications were found to be poor Apgar score, still birth, preterm labour and CMF.